The Economics Perspective of The Practice of MMM-Indonesia - Daris Purba (AFEBI Islamic Finance and Economic Review, 2017)
The MMM presence in Indonesia is becoming very popular because it promises a fantastic profit. Although covered by mutual-aid mode, not a few who perceive it as an investment business. Having observed the rapid development of the MMM as a new investment scheme, the researcher is driven to conduct a study on the economics perspective on the MMM. The objective of this research is to describe the practice of MMM-Indonesia and to review it from economics perspective.This study belongs to qualitative study with the descriptive-empirical approach. The informants were 4 MMM national top-leaders, a manager, a victim, and a new member. The methods of data collection used were preliminary survey, literature studies, interviews and observation. The data were analyzed using the descriptive analysis technique.The result of the study shows that MMM-Indonesia practice pyramid scheme, Ponzi scheme, and money game in its system. The research concludes that Indonesian government is unaware of the existence of this scheme threat and does no action against it. The study also concludes that the practice of MMM-Indonesia is incompatible with economics theories.The author suggests that the Indonesian government must ban the practice of the MMM as it is a threat to national economic growth and stability. The author suggests other researchers to do further research on the server, moderator, administrator, and company management of the MMM.Keywords: Economics, MMM, Ponzi Scheme, Pyramid Scheme